2018
DOI: 10.4081/aiua.2018.2.112
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the American Society of Anesthesiology classification scores on complications associated with percutaneous nephrolithotomy

Abstract: We believe that PCNL operation can be performed effectively and safely in both ASA3 patients and patients above the age of 65 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Ancak daha az morbiditeye neden olan RİRC de tekrarlayan seanslarla benzer başarıyı sağlayabilmektedir (3,4). PNL'nin daha fazla komplikasyona ve morbiditeye neden olduğunu belirten çalışmalar olduğu gibi Amerikan Anesteziyoloji Derneği skoru ASA-3 olan riskli hastalarda bile güvenle uygulanabileceğini bildiren çalışmalar da literatürde bulunmaktadır (3,(5)(6)(7) (12). Çalışmamızda da hem primer hem sekonder hasta grubunda yükseköğrenim almış grup sadece yaklaşık %15'lik dilimi oluşturmaktadır.…”
Section: Discussionunclassified
“…Ancak daha az morbiditeye neden olan RİRC de tekrarlayan seanslarla benzer başarıyı sağlayabilmektedir (3,4). PNL'nin daha fazla komplikasyona ve morbiditeye neden olduğunu belirten çalışmalar olduğu gibi Amerikan Anesteziyoloji Derneği skoru ASA-3 olan riskli hastalarda bile güvenle uygulanabileceğini bildiren çalışmalar da literatürde bulunmaktadır (3,(5)(6)(7) (12). Çalışmamızda da hem primer hem sekonder hasta grubunda yükseköğrenim almış grup sadece yaklaşık %15'lik dilimi oluşturmaktadır.…”
Section: Discussionunclassified
“…Even in the elderly, the fact that grade III-IV complications are below 3% reinforces this situation. Most complications in elderly patients with high comorbidity and anesthesia risk, as in young people, are based on the Grade I-II of classification of modified the Clavien and/or Grade I-II of the Satava system [19-21]. The multivariate logistic regression analysis of demonstrating factors predicting complications showed that the presence of residual stone and operation time are the most crucial factor in the elderly group.…”
Section: Discussionmentioning
confidence: 99%
“…This system could be used to choose the type of anesthesia and to assess the tolerance of patients to various surgical manipulations such as surgical position. Staying in a prone position during PCNL could lead to some difficulties, such as those in controlling the airway and maintaining the vascular access and ventilation of patients with lung diseases ( 4 ).…”
Section: Introductionmentioning
confidence: 99%